Angiography‐Based Index of Microcirculatory Resistance in Assessing the MVO and Infarct Size in STEMI Patients - Tian Wu; Xiaojiao Zhang; Chen Li; Yumeng Hu; Mengying Dong; Jiaqi Chai; Inam Ullah; Han Xu; Pengsheng Chen; Huiping Xu; Xiaoru Cheng; Xiaoxuan Gong; et al. (Clinical Cardiology, 2026)
ABSTRACT Objectives To evaluate angiography‐based index of microcirculatory resistance (angio‐IMR) in assessing microvascular obstruction (MVO) and infarct size (IS) in ST‐segment elevation myocardial infarction (STEMI). Background The effect of thrombolysis on post‐percutaneous coronary intervention (PCI) angio‐IMR, and its associations with MVO and IS remains unclear. Methods One hundred twenty‐three STEMI patients randomized to receive 5 mg intravenous bolus of recombinant staphylokinase (r‐SAK) or normal saline (NS) before PCI were recruited. Angio‐IMR was computed in infarct‐related arteries. MVO and IS were detected by cardiac magnetic resonance imaging. Results Compared with NS group, r‐SAK group exhibited numerically lower post‐PCI angio‐IMR (39.12 U vs. 42.57 U; p = 0.567), MVO (54.0% vs. 70.9%; p = 0.059), MVO extent (0.70% vs. 1.90%; p = 0.101) and IS (21.30% vs. 24.50%; p = 0.079). Post‐PCI angio‐IMR was positively correlated with MVO extent ( ρ = 0.347; p < 0.001) and IS ( ρ = 0.324; p < 0.001). Receiver operating characteristic analyses showed moderate diagnostic performance of angio‐IMR for MVO (area under the curve [AUC] = 0.750; p < 0.001), MVO > 2.6% (AUC = 0.735; p < 0.001) and IS > 25% (AUC = 0.712; p < 0.001). The exploratory optimal cut‐off values for these endpoints were approximately 40 U. Conclusions In STEMI patients, a single bolus of r‐SAK before PCI was associated with numeric reductions in post‐PCI angio‐IMR, MVO, MVO extent and IS. Additionally, angio‐IMR exhibited a significantly positive correlation with both MVO extent and IS, demonstrating the diagnostic value of this wire‐free method for assessing microvascular injury.